Electrical mechanisms for carrier compensation in homoepitaxial nonpolar m-ZnO doped with nitrogen. (4th February 2016) - Kurtz, A; Hierro, A; Lopez-Ponce, M; Tabares, G; Chauveau, J M
Abstract: By combining photoluminescence, capacitance-voltage profiling and deep level optical spectroscopy, the optical and electrical signatures of the deep levels induced by N in MBE-grown homoepitaxial m-ZnO layers are identified and correlated to different physical origins. The films are electrically compensated, with carrier concentrations that decrease from ∼1 · 10 16 cm −3 to ∼2 · 10 15 cm −3 as a result of increasing N incorporation. Regardless of the presence of N, an intrinsic trap is found in all films at EV  + 0.25 eV, most likely related to VZn defects. More interestingly, N induces three new deep levels close to the valence band whose bandgap position is electrically observed to be at EV  + 0.48 eV, EV  + 0.17 eV and EV  + 0.12 eV. The deepest trap at EV  + 0.48 eV correlates well with a N-induced level observed in previous studies on both ZnMgO and ZnO films. The EV  + 0.17 eV trap behaves as a minority (hole) carrier trap, and can be uniquely correlated with the acceptor level involved in the N-induced DAP emission observed in the photoluminescence spectra. Finally, the shallowest level at EV  + 0.12 eV shows an electrical signature completely distinguishable from the EV  + 0.17 eV level, and dominates the deep level spectra after N-incorporation with a trap concentration of ∼1.2 · 10 15 cm −3 .